Halal Supply Chain untuk Meningkatkan Jaminan Halal pada Pedagang Kuliner di Daerah Pesisir Pantai Kabupaten Pacitan - Nafi'ah, Dini Latifatun; Zahiroh, Mun Yah (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The Halal Supply Chain is a supply chain system that ensures the halal status of products from raw materials, production processes, storage, to serving to customers. This practice is generally carried out to meet economic needs or increase income. However, its implementation is not only an effort to maintain business continuity, but also a form of moral responsibility for business actors in ensuring that the products produced comply with Sharia principles. In the coastal areas of Pacitan Regency, the implementation of the Halal Supply Chain is very important to maintain consumer trust, especially among Muslim tourists, and to support the development of Halal tourism by enhancing Halal assurance in local culinary businesses. This study uses a qualitative approach with a field research method. Data were collected through interviews, observations, and documentation. Interviews were conducted with ten informants, consisting of two coastal area managers, six culinary traders, and two consumers, to obtain information and opinions from informants regarding the implementation of the Halal Supply Chain among culinary traders in the Pacitan coastal area. Data analysis was carried out through stages of data collection, reduction, presentation, and drawing conclusions to obtain a comprehensive overview of the practice of implementing Halal in the culinary business supply chain. The research results show that culinary traders on the coastal areas of Pacitan Regency have made efforts to implement the principles of the Halal Supply Chain through the selection of Halal raw materials, the separation of production tools, and maintaining the cleanliness of their business premises. Although some traders do not yet have Halal certification, awareness of the importance of Halal assurance is increasing along with the demand from consumers and Muslim tourists. The implementation of the Halal supply chain has been proven to boost buyer confidence, strengthen competitiveness, and promote the sustainability of local culinary businesses in accordance with Sharia economic principles.